2016
DOI: 10.15171/jcvtr.2016.03
|View full text |Cite
|
Sign up to set email alerts
|

Association between type 2 diabetes mellitus, biochemical factors and UCSNP-43 polymorphisms of CALPIN-10 gene in patients with atherosclerosis of coronary artery disease in Southern Iran population

Abstract: Introduction: Genetic variations in the calpain 10 gene (CALPIN-10), single nucleotide polymorphisms-43 (SNP-43), have increased the risk of type 2 diabete mellitus (T2DM) and coronary artery disease (CAD). Methods: We studied the control and CAD groups for association of association of SNP-43 in the CALPIN-10 gene with T2DM and other risk factors of its complications. Overall, we examined 452 individuals, 224 patients with CAD and 228 healthy subjects for CAD in Iranian population. All the subjects were geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…So far, researches on genetic factors of CAD have been performed in general populations and revealed new loci associated with CAD. Meanwhile, a few convincing studies suggested that some genes affect both atherosclerosis and diabetes [ 9 ]. Interestingly, a number of the studies including some of ours have shown that CAD risk may be partially different in diabetic individuals than in general population in terms of genetic susceptibility [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, researches on genetic factors of CAD have been performed in general populations and revealed new loci associated with CAD. Meanwhile, a few convincing studies suggested that some genes affect both atherosclerosis and diabetes [ 9 ]. Interestingly, a number of the studies including some of ours have shown that CAD risk may be partially different in diabetic individuals than in general population in terms of genetic susceptibility [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…DM is estimated to affect around 350 million people all over the world,[ 32 ] and coronary heart disease which is one of diabetic complications is considered a major cause of mortality and morbidity in Middle East populations. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Other genes are the basis for T2DM and DN; one of the genes is calcium-activated neutral protease-10 (CALPIN-10), a gene located at 2q37 that encodes for a non-lysosomal cysteine protease composed of 672 amino acids [8]. The Calpain-10 gene was the first diabetes gene identified by cloning and encoding the Calpain-10 protein [9].…”
Section: Introductionmentioning
confidence: 99%